Expanding the Pediatric Neuro-Oncology Teleconference Experience: From Twinning to International Cases Discussions - Essra' Al Badarin; Omar Chamdine; Moatasem Elayadi; Abeer Al-Battashi; Mohammed Al Nuaimi; Eman Taryam Alshamsi; Laila Hessissen; Hiba Al-Tarrah; Eslam Maher; Roula Farah; Ata Maaz; Waleed Said; et al. (JCO Global Oncology, 2025)
PURPOSEVideo teleconferencing in neuro-oncology is feasible and sustainable. The well-established, 20-year long monthly teleconference between King Hussein Cancer Center (KHCC), Jordan, and SickKids, Canada, is an example. Since 2018, several regional centers joined these meetings to discuss their patients' management plans. We aim to evaluate this experience.METHODSWe reviewed the minutes of 56 meetings (2018-2023). Preconference local treatment plans were compared with postconference recommendations. We documented the implementation of recommendations and the impact perceived by the treating oncologists.RESULTSTwo hundred fifty-one patients were discussed: 137 from Jordan and 114 from eight other countries. Four of the 14 participating oncologists had formal pediatric neuro-oncology training. Of the 227 patients (90%), where the local multidisciplinary team had suggested a preconference plan, the teleconference recommendations concurred with the proposed plan in 50% of cases, agreed on it and proposed an alternative option in 18%, and disagreed in 32%. The difference in recommendations mostly affected the proposed treatment modality. In 64% of discordant plans and 50% of alternative plans, the treating team applied the recommendations. The main challenges in applying the recommendations were attributed to patient-related factors (51%), local team consensus on a different plan (26%), or logistic difficulties (23%). The high patient load, longer involvement in teleconferencing, formal neuro-oncology training, and well-established multidisciplinary team helped the KHCC team formulate more concordant plans.CONCLUSIONThis experience illustrates the potential benefit for physicians to get an expert opinion on challenging cases. The participating oncologists valued the shared educational experience, especially those related to molecular testing and treatment implications. Joining such regional teleconferences is of particular importance to centers with small patient volume or those lacking a pediatric neuro-oncologist.